2009
DOI: 10.1002/mas.20238
|View full text |Cite
|
Sign up to set email alerts
|

Microchip technology in mass spectrometry

Abstract: Microfabrication of analytical devices is currently of growing interest and many microfabricated instruments have also entered the field of mass spectrometry (MS). Various (atmospheric pressure) ion sources as well as mass analyzers have been developed exploiting microfabrication techniques. The most common approach thus far has been the miniaturization of the electrospray ion source and its integration with various separation and sampling units. Other ionization techniques, mainly atmospheric pressure chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
95
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 271 publications
0
95
0
Order By: Relevance
“…UV absorbance detection, commonly applied in classical CE [4], is challenging in chip-based microfluidics [5,6] mainly due to the limited optical path length. Various detection methods have been implemented in MCE, the most common are electrochemical [7][8][9], mass spectrometric [10][11][12] and fluorescence-based [13,14] techniques. Fluorescence is the most successful method due to its relative ease of implementation and the unsurpassed sensitivity even enabling detection at single molecule level.…”
Section: Introductionmentioning
confidence: 99%
“…UV absorbance detection, commonly applied in classical CE [4], is challenging in chip-based microfluidics [5,6] mainly due to the limited optical path length. Various detection methods have been implemented in MCE, the most common are electrochemical [7][8][9], mass spectrometric [10][11][12] and fluorescence-based [13,14] techniques. Fluorescence is the most successful method due to its relative ease of implementation and the unsurpassed sensitivity even enabling detection at single molecule level.…”
Section: Introductionmentioning
confidence: 99%
“…A clear trend in on-chip integrated electrospray emitters was observed. In electrospray ionisation (ESI), reducing emitter aperture size is actively being pursued (Arscott and Troadec 2005;Mery et al 2008;Gibson et al 2009;Sikanen et al 2010), because of smaller droplets being generated. The enhanced ionisation efficiency obtained is of use to proteomics (Valaskovic et al 1995) and metabolomics.…”
Section: Introductionmentioning
confidence: 99%
“…Additional features such as pneumatic nebulizers have been incorporated to enhance emission [44,54,55]. Reviews of lab-on-a-chip nanoelectrospray sources can be found in [56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%